Gloria Swanson : Ready for Her Close-Up - Welsch, Tricia (Book collections on Project MUSE., 2013)
This book shows how a talented, self-confident actress negotiated a creative path through seven decades of celebrity. It also illuminates a little-known chapter in American media history: how the powerful women of early Hollywood transformed their remarkable careers after their stars dimmed. This book brings Swanson back into the spotlight, revealing her as a complex, creative, entrepreneurial, and thoroughly modern woman. Swanson cavorted in slapstick short films with Charlie Chaplin and Mack Sennett in the 1910s. The popularity of her films with Cecil B. DeMille helped create the star system. A glamour icon, Swanson became the most talked-about star in Hollywood, earning three Academy Award nominations, receiving 10,000 fan letters every week, and living up to a reputation as Queen of Hollywood. She bought mansions and penthouses, dressed in fur and feathers, and flitted through Paris, London, and New York engaging in passionate love affairs that made headlines and caused scandals. Frustrated with the studio system, Swanson became a talented businesswoman who patented inventions and won fashion awards for her clothing designs; a natural foods activist; an exhibited sculptor; and a designer employed by the United Nations. All the while she continued to act in films, theater, and television at home and abroad. --